Pengembangan Anestesi Rekam Medis Elektronik (AREME) untuk Dokumentasi Asuhan Keperawatan Anestesiologi - Abadi, Bagus Wahyu; Cing, Marta Tania Gabriel Ching; Hardiyani, Tati; Annisa, Rully (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
The role of anesthesia nurses in the anesthesiology nursing care process is crucial in providing care to patients. One essential aspect that should not be overlooked in this process is documentation. Anesthesiology nursing care documentation (ASKAN) is a record that documents all actions performed by anesthesia nurses on patients. Students of the D4 Anesthesiology Nursing Program at Universitas Muhammadiyah Purwokerto face several challenges in using conventional reporting methods. This study aims to develop a nursing care documentation method using information technology through a computer-based application. The research and development method was employed in this study to design the application. Observations and interviews with students of the D4 Anesthesiology Nursing Program at Universitas Muhammadiyah Purwokerto were conducted to explore the researched phenomenon. The researchers designed the Anesthesia Electronic Medical Record (AREME) application for recording and documenting anesthesiology nursing care electronically. The development of the AREME application follows anesthesiology nursing care standards based on the ASKAN guidelines. The implementation of AREME in ASKAN documentation demonstrates that this application can facilitate the documentation process, which was previously conducted conventionally.